Young People and Church Since 1900: Engagement and Exclusion - Thompson, Naomi (AHRC/ESRC Religion and Society Series, 2017)
Cover ; Half Title ; Title Page ; Copyright Page ; Table of Contents; List of illustrations; Acknowledgements; 1. Introduction: Postmodernism, institutionalisation, and social currencies; Collecting the historical narratives; Collecting the contemporary narratives; Analysing the narratives; Sample; The postmodern approach: Epistemes, discourses, and narratives; Social and spiritual currencies; The changing context of Christianity in twentieth-century England; Three key themes; Outline of the book; 2. From Raikes' revolution to rigid institution: Sunday Schools in twentieth-century England.